Optimalisasi Kinerja Perusahaan melalui Transformasi Digital, Kemampuan Manajerial, dan Intensitas R&D dengan Moderasi Koneksi Politik - Putri, Amelia; Widodo, Condro; Suryaningrum, Diah Hari (Universitas Gorontalo, 2025)
This study aims to analyze the effects of digital transformation, managerial capability, and RD intensity on firm performance, with political connections as a moderating variable. The research uses 105 financial reports from companies listed on the Indonesia Stock Exchange (IDX) and employs the SEM-PLS analysis method. The results show that digital transformation and managerial capability have a negative and significant effect on firm performance, while RD intensity has a positive and significant effect. Furthermore, political connections strengthen the effect of digital transformation on firm performance. These findings indicate that poorly managed digital transformation and limited managerial capability can reduce firm performance, whereas investment in RD enhances competitiveness.